Web-Based Online Sales Information System Design: Perancangan Sistem Informasi Penjualan Online Berbasis Web - Pradita, Arsha Setya; Sumarno, Sumarno (Universitas Muhammadiyah Sidoarjo, 2022)
In the current era of globalization, the advancement of information systems is now very much needed because it can facilitate performance in a company, one of which is in the online sales business. PT Safra Asia Gemilang is a large company engaged in the sale of cosmetics and nutrition, in selling its products it still uses a manual system. So we need a system that is useful for simplifying and accelerating sales of the company's products. Therefore, the purpose of this research is to design a system, namely the Design of a Web-Based Online Sales Information System at PT Safra Asia Gemilang. The system development method used in this study is the Waterfall Method. The data collection stage used was literature study, observation, and interviews. PHP is a programming language in making the system, and MySQL as the database. The results of system testing from this study using blackbox testing by providing input to the program indicate that the features in the system have no errors and are running according to function very well.